2009
DOI: 10.1016/j.cmpb.2009.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A minimal model of lung mechanics and model-based markers for optimizing ventilator treatment in ARDS patients

Abstract: A majority of patients admitted to the Intensive Care Unit (ICU) require some form of respiratory support. In the case of Acute Respiratory Distress Syndrome (ARDS), the patient often requires full intervention from a mechanical ventilator. ARDS is also associated with mortality rate as high as 70%. Despite many recent studies on ventilator treatment of the disease, there are no well established methods to determine the optimal Positive End Expiratory Pressure (PEEP) or other critical ventilator settings for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 35 publications
(52 reference statements)
0
62
0
Order By: Relevance
“…While numerical integration coupled with gradient based identification methods are frequently used successfully (Sundaresan et al 2009;Schranz et al 2011), it is important to know the limitations of such methods. In particular, this investigation has shown that numerical integration methods which handle discontinuities poorly, such as the proprietary MATLABTM methods, are likely to cause parameter identification failure when poorly applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerical integration coupled with gradient based identification methods are frequently used successfully (Sundaresan et al 2009;Schranz et al 2011), it is important to know the limitations of such methods. In particular, this investigation has shown that numerical integration methods which handle discontinuities poorly, such as the proprietary MATLABTM methods, are likely to cause parameter identification failure when poorly applied.…”
Section: Discussionmentioning
confidence: 99%
“…This information can be used to guide therapy or aid diagnosis (Sundaresan et al 2009;Lozano et al 2008;Chase et al 2011). However, fitting a model simulation to measured data often requires complex mathematical algorithms, and success is not guaranteed.…”
Section: Introductionmentioning
confidence: 99%
“…In the model, the lung unit can assume only two possible states: recruited (or open) and derecruited (or closed) [17], [20]. These two states are governed only by the threshold opening pressure (TOP), which is the critical pressure above which the lung unit pops open, and the threshold closing pressure (TCP) below which the unit collapses.…”
Section: A Model Of the Lung Mechanicsmentioning
confidence: 99%
“…These two states are governed only by the threshold opening pressure (TOP), which is the critical pressure above which the lung unit pops open, and the threshold closing pressure (TCP) below which the unit collapses. The model uses normally distributed TOP and TCP pressures with a specific mean and standard deviation (SD), which may be adjusted to reflect the heterogeneous characteristic of alveoli under different abnormal lung conditions such as ARDS [20], [21]. Fig.…”
Section: A Model Of the Lung Mechanicsmentioning
confidence: 99%
“…The linear portion of the static PV curve is where most of the data points occur on any measured dynamic PV loop. Based on the work of Sundaresan et al [23], over 90% of the data points from measured PV loops occur in the static portion of the static PV curve and are the points primarily used in this analysis. The non-linear portions at PEEP and PIP are actually high flow regions and are thus do not account for or include the majority of the data.…”
Section: Limitationsmentioning
confidence: 99%